The Infection of the Japanese Encephalitis Virus SA14-14-2 Strain Induces Lethal Peripheral Inflammatory Responses in IFNAR Deficiency Mice - Liu, Juan; Jing, Wenxian; Fang, Yongxiang; He, Xiaobing; Chen, Guohua; Jia, Huaijie; Wang, Jingyu; Jing, Zhizhong (Frontiers in Microbiology, 2022)
The Japanese encephalitis virus (JEV) is a leading cause of mosquito-borne viral encephalitis worldwide. Clinical symptoms other than encephalitis, on the other hand, are substantially more prevalent with JEV infection, demonstrating the relevance of peripheral pathophysiology. We studied the peripheral immunopathogenesis of JEV using IFNAR deficient (IFNAR-/-) mice infected with the SA14-14-2 strain under the BSL-2. The body weight and survival rate of infected-IFNAR-/- mice decreased significantly. Infected-IFNAR-/- mice's liver and spleen demonstrated obvious tissue damage and inflammatory cell infiltration. There was also extensive viral replication in the organs. IFN-α/β protein expression was dramatically elevated in peripheral tissues and serum, although the related interferon-stimulated genes (ISGs) remained low in the spleen and liver of infected-IFNAR-/- animals. Consistently, the differentially expressed genes (DEGs) analysis using RNA-sequencing of spleens showed inflammatory cytokines upregulation, such as IL-6, TNF-α, and MCP-1, and IFN-γ associated cytokine storm, and.the infiltration of macrophages and neutrophils in the spleen and liver of SA14-14-2-infected IFNAR-/- mice was dramatically elevated. However, there was no significant difference in tissue damage, viral multiplication, or the production of IFN-α/β and inflammatory cytokines in the brain. Infection with the JEV SA14-14-2 strain resulted in a lethal peripheral inflammatory response and organ damage without encephalitis in IFNAR-/- mice. Our findings may help shed light on the peripheral immunopathogenesis associated with clinical JEV infection and aid in developing treatment options.